Phenotypic divergence in sunflower genotypes (Revista de Ciências Agroveterinárias, 2012)
The objective of this work was to evaluate the phenotypic divergence among 17 genotypes of sunflower. The experiment was carried out in Papanduva, North Plateau of Santa Catarina State, Brazil, in 2008/2009 cropping season. The experimental design was a randomized block with four replications. The multivariate was used to evaluate the divergence among the genotypes by canonic variable and cluster analysis, based on the generalized Mahalanobis Distance (D2). Univariate and multivariate analyses of variance showed differences among genotypes. The genotypes were grouped in tree clusters. The plant height to the 70 days after the sowing and yield grains showed high contribution towards phenotypic divergence.
Keywords: Variability; Helianthus annus; D² analysis.